PENGARUH ARUS KAS TERHADAP FINANCIAL DISTRESS PADA MASA SEBELUM DAN SAAT PANDEMI COVID-19 (Studi Empiris pada Sektor Industri Hotel, Restoran, dan Pariwisata di Indonesia) - Purba, Mikhael Christopel; Achmad, Tarmizi (Diponegoro Journal of Accounting, 2023)
This research is to test and analyze the effect of Operating Cash Flow, Investing Cash Flow, and Financing Cash Flow to Financial Distress. Considering the existence of this unprecedented situation is useful for understanding how influential is cash flow on financial distress. The population of this research is all hotel, restaurant and tourism sub-sector companies before and during the pandemic of Covid-19 listed in the Indonesian Stock Exchange. The sample was selected based on predetermined purposive sampling criteria on 26 companies for 4 years of observation from 2018 until 2021. This research uses data obtained from the official website of the company and the Indonesian Stock Exchange in the form of annual financial reports. This research was carried out using multiple linear regression with SPSS 21. The data analysis method used descriptive analysis, classical assumption test, and hypothesis testing.The result of the research showed that Operating Cash Flow has a negative effect on financial distress before and during the Covid-19. Investing Cash Flow has a positive effect before and during the pandemic of Covid-19. But for Financing Cash Flow it had no significant effect before and during pandemic Covid-19.